Network performance analysis research in storage area networks - Yew, Rui Xiong. (2010)
Servers in data centres today require multiple connections to connect to various networks, resulting in limitations for network expansion due to space limitations. Fibre Channel (FC) over Ethernet (FCoE) is a new technology that aims to achieve server input/output consolidation by merging Ethernet network traffic and storage network traffic, thereby reducing number of physical connections and achieve lower cooling costs. This project is to explore the implementation of FCoE network and its impact on performance when accessing a storage area network, where Fibre Channel has been dominating the scene. Firstly, a background study of SAN, FCoE, Ethernet network and some tools for benchmarking is done. After which, an initial conceptualization of the physical infrastructure is proposed, followed by documentation of the setup processes. The project ends with discussion and analysis of the results obtained from benchmarking. Recommendations are also made on how the project can be extended to achieve extensive evaluation of FCoE.